Fibroblast growth factor-21 alleviates phenotypic characteristics of dry age-related macular degeneration in mice. (May 2022) - Zhao, Tingting; Wang, Wenfei; Gao, Kun; Li, Siming; Jiang, Ye; Yang, Zhifeng; Liu, Jiannan; Wang, Yanli; Peng, Shaomin
Abstract: Age-related macular degeneration (AMD) is the main cause of blindness in elderly individuals. As a metabolic regulator, fibroblast growth factor 21 (FGF-21) has been proven indicated to have an effect on wet AMD, but whether this cytokine has a therapeutic effect on dry AMD is unclear. The current study aimed to evaluate the preventive effects of FGF-21 against retinal degeneration in mice and provide mechanistic insights. FGF-21−/− mice were raised to 10 months of age. Then, the morphological changes in the retinal pigment epithelium (RPE)/choroid of the mice were observed by transmission electron microscopy (TEM), and iTRAQ was used to detect the variations in the protein profile. Next, FGF-21−/− and wild-type mice of the same age were fed hydroquinone to generate a dry AMD mouse model to examine whether exogenous FGF-21 can interfere with the occurrence and development of dry AMD. In vivo studies revealed that following FGF-21 knockout, there was an increase in the expression of complement in the RPE/choroid concomitant with the occurrence of dry AMD-like pathological changes. Furthermore, exogenous FGF-21 administration effectively reversed this phenomenon. FGF-21 also demonstrated strong anti-inflammatory effects in the RPE/choroid by inhibiting the NF-κB pathway. In conclusion, the present study demonstrates that FGF-21 treatment presents a novel therapeutic approach for the prevention and development of dry AMD by reducing complement. Highlights: Fibroblast Growth Factor 21 Deficiency Induces Dry AMD in Mice by Elevating Complement in the Eye. FGF-21 has a novel therapeutic approach for the prevention of dry AMD development via reducing inflammatory process induced by NF-kB pathway.